FENOMENA POKOK PENDIDIKAN INDONESIA: APA DAN BAGAIMANA? - I Wayan Dana Ardika; A.A. Raka Sitawati; Ni Ketut Suciani (Soshum: Jurnal Sosial dan Humaniora, 2013)
The development of education is one priority in the national development agenda. The development of education is very important because it shows significant role in achieving progress in many aspects of life; such as social, economic, political, and cultural. Therefore, the Government is obliged to fulfill the right of every citizen in obtaining educational services to improve the quality of life of the Indonesian people as mandated by the 1945 Constitution, which requires that the government is responsible for creating the intellectual life of the nation and the general welfare. Having enjoyed a dozen years of education in Indonesia makes us feel sad and less satisfied. Assessments were done more based on results-oriented, not by process. Guidance to the students often ignore EQ (Emotional Quotient) and SQ (Spiritual Quotient), education practitioners only emphasizes the IQ (Intellectual Quotient). In this paper presented three central issues: i) improving quality, ii) equity of access, and iii) the efficiency of the education budget. The research analyzed by descriptive qualitative. There are still many things that must be addressed related to the national education system. Educational equity that is currently lacking a well realized. The problem is because education itself is oriented in urban areas and the subsidy from the government that was still not enough for students. The effort of the government in conducting educational equity for poor and remote areas in Indonesia is not enough with the 9- year compulsory education program and the procurement of information technology such as television, radio, and internet.